CompilerGym: Robust, Performant Compiler Optimization Environments for AI Research - Cummins, Chris; Wasti, Bram; Guo, Jiadong; Cui, Brandon; Ansel, Jason; Gomez, Sahir; Jain, Somya; Liu, Jia; Teytaud, Olivier; Steiner, Benoit; Tian, Yuandong; Leather, Hugh (2022 IEEE/ACM International Symposium on Code Generation and Optimization (CGO), 2022)
Interest in applying Artificial Intelligence (AI) techniques to compiler optimizations is increasing rapidly, but compiler research has a high entry barrier. Unlike in other domains, compiler and AI researchers do not have access to the datasets and frameworks that enable fast iteration and development of ideas, and getting started requires a significant engineering investment. What is needed is an easy, reusable experimental infrastructure for real world compiler optimization tasks that can serve as a common benchmark for comparing techniques, and as a platform to accelerate progress in the field.We introduce CompilerGym, a set of environments for real world compiler optimization tasks, and a toolkit for exposing new optimization tasks to compiler researchers. CompilerGym enables anyone to experiment on production compiler optimization problems through an easy-to-use package, regardless of their experience with compilers. We build upon the popular OpenAI Gym interface enabling researchers to interact with compilers using Python and a familiar API.We describe the CompilerGym architecture and implementation, characterize the optimization spaces and computational efficiencies of three included compiler environments, and provide extensive empirical evaluations. Compared to prior works, CompilerGym offers larger datasets and optimization spaces, is 27× more computationally efficient, is fault-tolerant, and capable of detecting reproducibility bugs in the underlying compilers.In making it easy for anyone to experiment with compilers - irrespective of their background - we aim to accelerate progress in the AI and compiler research domains.